OPTIMASI PARAMETER KARBURISASI TEMPERATUR RENDAH PADA BAJA TAHAN KARAT AUSTENITIK MENGGUNAKAN METODE TAGUCHI - Annissa Fanya; Esa Haruman (Jurnal Rekayasa Mesin, 2022)
Austenitic stainless steel is a popular material for its corrosion resistant properties, however it has low hardness which limits its application. Low-temperature carburizing can be used to improve the mechanical properties of the austenitic stainless steel by producing expanded austenite layer. In order to get a high-quality layer and an efficient processing operation, the carburizing process must be optimized. In this research, a Taguchi method was utilized to investigate the effect of processing parameters related to the formation of the expanded austenite layer depth in austenitic stainless steel. Four factors were selected to be optimized namely temperature, gas flow rate, time, and gas composition with three levels each. L9(34) orthogonal array was applied with nine experimental tests to get the diffusion depth value of carbon in the expanded austenite layer. S/N ratio was used to determine the optimum factor combination with nominal-the-better quality characteristic and the most significant factor was obtained by applying the Analysis of Variance. Temperature was found to be the most significant factor with 54.91% contribution. The optimum combination was also successfully defined with temperature at 450°C (level 2), gas flow rate at 15 liter per minute (level 2), time at 12 hours (level 3), and gas composition at 15% CH4 – 5% H2 – 80% N2 (level 3). Clearly, in this study the Taguchi method was proven to be appropriately used as one of robust tools in optimizing the thermochemical treatment process parameters.